Art Music by Caribbean Composers: Dominica - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
The cultures and traditions of both the French and British colonizers have strong influence in Dominica. Both English and a French Creole are widely spoken (Bilby, 2005).Musical styles in Dominica include folk styles such as bélé; quadrille, influenced by French contradanse; and popular styles such as calypso and the local “cadence-lypso” (Guilbault, 1998).